Multilingual Theatre Voice Training in South Africa: Our Translingual Attempt Employing Lessac Kinesensics. Issue 2 (4th May 2019) - Munro, Marth; Lemmer, Karina
ABSTRACT: Teaching theatre voice in a multilingual paradigm (as present in South African education) is complex as it engages with various identities simultaneously. It is taken as given that people navigate their worlds through the use of language, where the language is contextual, meaning driven, identity forming, and affirming. Furthermore, such navigation differs from language to language, resulting in the potential for conflicting and conflictual navigations, power dynamics, conceptual differences, and other complexities. This is compounded when the language of learning differs from many of the first languages present in the classroom. This article presents the authors' attempts within the South African higher education environment to create a translingual learning space where inclusivity and diversity are acknowledged, affirmed, and actively utilized. The authors use a participatory action research project in which they draw on principles from Lessac Kinesensics to create and invite translingual explorations and learning opportunities. They specifically report on the construction and use of a Setswana workbook as a first formal step toward affirming translingual learning space, committing to and embracing transformation.